RESTRICTIONS SOCIAL LARGE SCALE AS EFFORTS TO CONTROL COVID- 19 PANDEMIC NATURE FROM HUMAN RIGHTS PERSPECTIVE - Lamria Fitriani Manalu (NOMOI Law Review, 2020)
State as stakeholders obligation to guarantee the rights of its people in the form of homage (to respect), protection (to protect) and fulfillment (tofulfill) without discrimination.The aim of this study was todetermine the Social RestrictionsBERswhenthe Greatas an effort totacklingthe pandemicCOVID-19in ahuman rights perspective, which is expected to be usefulas a reflection on the application ofPSBBin Indonesia.This research is descriptive analyticalusing data sources obtained throughliterature study, whiledata collection techniques and procedures were carried out through document study.Normative data were analyzedqualitatively.The results showed that the PSBB was carried out in accordance with predetermined criteria.Such restrictionsare in accordance with statutory regulations, in which the state may only impose restrictions on rights through the enactment of laws and the public has the right to enjoy the highest attainable standard of physical and mental health.The government has made various important efforts to protect the right to life, the right to self-development, and the rights to the welfare of the affected people.This means that thestate has carried out its obligations for health services and a healthy and healthy life foreveryone as mandated in the 1945 Constitution. The results show that the application of the PSBBas an effort totacklethe COVID-19 pandemic is not contradictory or is in accordance with a human rights perspective.Keywords:Restriction Social BerskalaBesar,COVID-10, HAM